Acanthosis Nigricans: relation to risk of Type 2 diabetes and cardiovascular diseases among Jamaican adolescents. Issue 2 (2016) - Barrett, Sheila C; Huffman, Fatma G; Johnson, Paulette; Campa, Adriana; Magnus, Marcia; Dalip, Dalip
No abstract available